Bioinformatics analysis identifies WNK1 gene as a potential biomarker for cholangiocarcinoma diagnosis and immune infiltration - Qi Sun; Xianli Lei; Xiangrong Meng; Caijun Zha; Lei Yan; Wenjing Zhang (Journal of Genetic Engineering and Biotechnology, 2024)
Background: Cholangiocarcinoma (CHOL) is a malignant epithelial carcinoma of the digestive system with poor prognosis and high mortality. WNK lysine deficient protein kinase 1 (WNK1) is known to be associated with tumorigenesis in various cancers. However, the relationship between WNK1 and CHOL development, as well as the potential mechanisms involved, remains poorly understood. Methods: Microarray datasets of CHOL (GSE22633 and GSE32879) were retrieved from the Gene Expression Omnibus (GEO) database. Functional enrichment and immunoinfiltration analyses were performed for genes co-expressed with WNK1. GraphPad Prism 9 was utilized for statistical data analysis and the construction of receiver operating characteristic (ROC) curves. The impact of WNK1 on the CHOL tumor microenvironment was analyzed using Tumor Immune Estimation Resource (TIMER), Venn diagrams, STRING, and TISIDB database for information on WNK1-related chemokines and chemokine receptors. Protein-protein interaction (PPI) networks were used to predict transcription factors and microRNAs interacting with WNK1 and the associated hub genes. Results: Differential expression of WNK1 was observed between CHOL and normal samples, suggesting its diagnostic value. Functional analysis showed that WNK1 and its associated genes were primarily enriched in pathways such as leukocyte transendothelial migration and chemokine signaling. Neutrophils were the only type of infiltrating immune cells associated with WNK1 in the CHOL tumor microenvironment (TME). VEGFA and ALB were identified as hub genes, and X-C motif chemokine receptor 1 (XCR1) and C-X-C motif chemokine ligand 5 (CXCL5) were identified as core chemokines and chemokine receptors related to WNK1 and neutrophil infiltration in CHOL. Conclusions: Based on network analysis and the summary of previous studies, it was proposed that CHOL tumor cells secrete CXCL5, leading to neutrophil recruitment to the tumor microenvironment. Vascular endothelial growth factor A (VEGFA) released by the infiltrating neutrophils is suggested to promote overexpression of WNK1 by tumor cells, activating the VEGFA downstream pathway to promote angiogenesis and tumor progression.